Remote support by multidisciplinary teams: A crucial means to cope with the psychological impact of the SARS‐COV‐2 pandemic on patients with cystic fibrosis and inflammatory bowel disease in Lombardia. Issue 7 (25th April 2021) - Nobili, Rita Maria; Gambazza, Simone; Spada, Maria Simonetta; Tutino, Anna Luisa; Bulfamante, Anna Marta; Mariani, Alessandra; Brivio, Anna; Moioli, Loredana; Rizzato, Erika; Sansotta, Naire; Claut, Laura; Faelli, Nadia; et al.
Abstract: Background: During Coronavirus Disease 2019 (COVID‐19) outbreak in Lombardia, people were recommended to avoid visiting emergency departments and attending routine clinic visits. In this context, it was necessary to understand the psychological reactions of patients with chronic diseases. We evaluated the psychological effects on patients with chronic respiratory conditions and inflammatory bowel disease (IBD) through the analysis of their spontaneous contacts with their referral centres. Methods: Cross‐sectional study was conducted from February 23 to April 27, 2020 in patients, or their parents, who contacted their multidisciplinary teams (MDT). E‐mails and phone calls directed to the MDT of the centre for cystic fibrosis (CF) in Milano and for paediatric IBD in Bergamo, were categorised according to their contents as information on routine disease management, updates on the patient's health status, COVID‐19 news monitoring, empathy towards health professionals, positive feedback and concern of contagion during the emergency. Results: One thousand eight hundred and sixteen contacts were collected during the study period. In Milano, where the majority of patients were affected by CF, 88.7% contacted health professionals by e‐mail, with paediatricians receiving the largest volume of emails and phone calls compared with other professionals ( P < .001). Compared with Milano, the centre for IBD in Bergamo recorded more expression of empathy towards health professionals and thanks for their activity in the COVID‐19 emergency (52.4% vs 12.7%, P < .001), as well as positive feedback (64.3% vs 2.7%, P = .003). Conclusion: One of the most important lessons we can learn from COVID‐19 is that it is not the trauma itself that can cause psychological consequences but rather the level of balance, or imbalance, between fragility and resources. To feel safe, people need to be able to count on the help of those who represent a bulwark against the threat. This is the role played, even remotely, by health professionals.